Community participation in creative tourism development in Klongdaen community, Southern Thailand - Ruangroengkulrit, Tidaporn (2019)
Creative tourism, which focuses on local culture conservation and learning experience in host culture, is considered as a tool to develop sustainable tourism. This study aims to explore the application of creative tourism in homestay communities in southern Thailand, identify factors affecting creative tourism development in homestay communities in southern Thailand, determine the extent of homestay community participation in creative tourism management in southern Thailand, and identify problems of creative tourism management and operation by homestay communities. Based on the potential to develop creative tourism of homestay communities in southern Thailand and three elements of creative tourism (creative space, creative cluster and creative spectacles), the homestay community, namely Klongdaen market, was selected. This study employed qualitative approach by applying semi-structured interview, observation and focus group discussion. The result shows that the application of creative tourism in Klongdaen market community used local capital, intellectual capital and human capital to create value for tourism products by applying historical uniqueness, local wisdom, culture and knowledge of community members to create tourism products such as creative tourism backdrop, events and workshops. In addition, each homestay community has different limitations for their participation in creative tourism management. In Kloangdaen, it is seen that factors affecting creative tourism development are context, local involvement and empowerment, strong leadership and a committed team, long-term planning, clear rules and objectives, partnership, communication and marketing strategy. Further, the management of the homestay community is in the form of coordination between communities. However, there are differences in the form of collaborative management and unity of the people in the community. The homestay community has creative tourism development patterns, starting with human capital, and also historical and social capital in the community to develop creative tourism products.